2021
DOI: 10.1097/01.hjh.0000745076.39504.af
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Healthy Vascular Ageing (Hva) and Early Vascular Ageing (Eva) in General Population. Eh-Uh Study (Croatian Scientific Foundation)

Abstract: Objective: Arterial stiffness (cfPWV) is acknowledged biomarker of ageing. It was reported that ePWV correlated almost identical with the measured cfPWV and had significant predictive value for cardiovascular (CV) events in hypertensive patients. In a subgroup of population ageing process is faster (EVA), while slower in subjects with HVA). Our aim was to analyze characteristics of EVA and HVA in general Croatian population using ePWV. Design and method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This significant rise might reflect several factors, including better cancer survival rates; an aging population; and the impact of cancer treatments, such as EGFR inhibitors, which can cause high blood pressure, on cardiovascular health [ 1 ]. There are numerous reasons for early vascular aging [ 81 ] and arterial stiffness can increase mortality in these patients [ 82 ]. Among these reasons, anthracyclines, alkylating agents, and TKIs are known to impact the elasticity of arterial walls.…”
Section: Reviewmentioning
confidence: 99%
“…This significant rise might reflect several factors, including better cancer survival rates; an aging population; and the impact of cancer treatments, such as EGFR inhibitors, which can cause high blood pressure, on cardiovascular health [ 1 ]. There are numerous reasons for early vascular aging [ 81 ] and arterial stiffness can increase mortality in these patients [ 82 ]. Among these reasons, anthracyclines, alkylating agents, and TKIs are known to impact the elasticity of arterial walls.…”
Section: Reviewmentioning
confidence: 99%
“…We have previously demonstrated that high levels of circulating reactive oxygen species (ROS) have a direct effect on retinal microvascular function [ 7 , 8 ]. Indeed, the evidence suggests that oxidative stress-induced cellular senescence is a key influencer of age-induced mechanical and structural vascular dysfunction [ 9 , 10 , 11 , 12 ] as well as of the development and progression of CVDs [ 13 , 14 , 15 , 16 , 17 ]. Additionally, high levels of ROS deplete the NO reserve, a well-known critical molecule in the regulation of vascular function and tone [ 18 ].…”
Section: Introductionmentioning
confidence: 99%